Chronic Rhinosinusitis in Children - Hassan H. Ramadan (Hindawi Limited, 2012)
Rhinosinusitis is a very common disease worldwide and specifically in the US population. It is a common disease in children but may be underdiagnosed. Several reasons may account to the disease being missed in children. The symptoms in children are limited and can be very similar to the common cold or allergic symptoms. Cough and nasal discharge may be the only symptoms present in children. A high index of suspicion is necessary to make the diagnosis of rhinosinusitis in these children. The majority of those children are treated medically. Only a few number will require surgical intervention when medical treatment fails. Complications of rhinosinusitis, even though rare, can carry a high morbidity and mortality rate.